Anakinra reduces blood pressure and renal fibrosis in one kidney/DOCA/salt-induced hypertension. (February 2017) - Ling, Yeong Hann; Krishnan, Shalini M.; Chan, Christopher T.; Diep, Henry; Ferens, Dorota; Chin-Dusting, Jaye; Kemp-Harper, Barbara K.; Samuel, Chrishan S.; Hewitson, Timothy D.; Latz, Eicke; Mansell, Ashley; Sobey, Christopher G.; et al.
Graphical abstract: Abstract: Objective: To determine whether a clinically-utilised IL-1 receptor antagonist, anakinra, reduces renal inflammation, structural damage and blood pressure (BP) in mice with established hypertension. Methods: Hypertension was induced in male mice by uninephrectomy, deoxycorticosterone acetate (2.4 mg/d, s.c. ) and replacement of drinking water with saline (1K/DOCA/salt). Control mice received uninephrectomy, a placebo pellet and normal drinking water. 10 days post-surgery, mice commenced treatment with anakinra (75 mg/kg/d, i.p. ) or vehicle (0.9% saline, i.p. ) for 11 days. Systolic BP was measured by tail cuff while qPCR, immunohistochemistry and flow cytometry were used to measure inflammatory markers, collagen and immune cell infiltration in the kidneys. Results: By 10 days post-surgery, 1K/DOCA/salt-treated mice displayed elevated systolic BP (148.3 ± 2.4 mmHg) compared to control mice (121.7 ± 2.7 mmHg; n = 18, P < 0.0001). The intervention with anakinra reduced BP in 1K/DOCA/salt-treated mice by ∼20 mmHg (n = 16, P < 0.05), but had no effect in controls. In 1K/DOCA/salt-treated mice, anakinra modestly reduced (∼30%) renal expression of some (CCL5, CCL2; n = 7–8; P < 0.05) but not all (ICAM-1, IL-6) inflammatory markers, and had no effect on immune cell infiltration (n = 7–8, P > 0.05). Anakinra reduced renal collagen content (n = 6, P < 0.01) but paradoxically appeared to exacerbate the renal and glomerular hypertrophy (n = 8-9, P < 0.001) that accompanied 1K/DOCA/salt-induced hypertension. Conclusion: Despite its anti-hypertensive and renal anti-fibrotic actions, anakinra had minimal effects on inflammation and leukocyte infiltration in mice with 1K/DOCA/salt-induced hypertension. Future studies will assess whether the anti-hypertensive actions of anakinra are mediated by protective actions in other BP-regulating or salt-handling organs such as the arteries, skin and brain.